Gender difference with the use of percutaneous left ventricular assist device in patients undergoing complex high-risk percutaneous coronary intervention: From pVAD Working Group. Issue 4 (June 2019) - Doshi, Rajkumar; Singh, Avneet; Jauhar, Rajiv; Meraj, Perwaiz M
Background: The interventional treatment of complex high-risk indicated patients is technically difficult and can result in poor outcomes. Thus, percutaneous left ventricular assist devices are being increasingly used to provide hemodynamic support. No data is available comparing male and female for Complex High-risk Indicated Patients treated with percutaneous left ventricular assist devices. Our goal was to evaluate in-hospital as well as short term outcomes comparing males and females. Methods: There were 160 complex high-risk indicated patients with percutaneous left ventricular assist device use who were not in cardiogenic shock. A total of 132 male and 28 female patients were included. Ejection fraction below 35% with one additional criterion such as use of atherectomy device or treatment on unprotected left main disease or multi-vessel disease were our inclusion criteria. An Impella 2.5 or Impella CP (Abiomed Inc.) device was used as a left ventricular support device. Results: There was no difference in in-hospital mortality between the genders after performing a propensity score matched analysis (8.3% vs . 12.5%, p =0.54). Secondary outcomes of myocardial infarction, cardiogenic shock, congestive heart failure, dysrhythmia, major adverse cardiac events and composite of all complications were higher in males. Furthermore, 30-day survival was similar in males and females (88.9% vs . 87.5%, p =0.31). In addition, worse complications rates and survival were noted in patients with incomplete revascularization compared with those patients with complete revascularization in both gender. Conclusion: This study demonstrated no gender difference in clinical outcomes when using percutaneous left ventricular assist device support for the treatment of complex high-risk indicated patients. Overall, males had higher secondary outcomes compared with females with no difference in in-hospital mortality or 30-day survival rates.